2006
DOI: 10.1016/j.jasms.2005.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of gas phase ion structure for proline-containing b2 ion

Abstract: Unusual fragmentation was observed for doubly charged VPDPR in which cleavage Cterminal to proline and N-terminal to aspartic acid yielded b 2 (ϩ a 2 )/y 3 complementary ions. This unique fragmentation is contradictory to trends previously established by statistical analysis of peptide tandem mass (MS/MS) spectra [1][2][3][4]. Substitution of alanine for aspartic acid (i.e., VPAPR) did not change the fragmentation, indicating the cleavage was not directed by aspartic acid. Fragmentation patterns for VPAPR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…Again, elimination of the neutral Tyr imine (135 u) to form m/z 100 is the major primary fragmentation pathway. A similar result has been reported by Wysocki and co-workers [47], who observed that the b 2 ion derived from Val-(N-methyl-Ala)-AlaPro-Arg fragmented exclusively by loss of a neutral of 71 u, which was shown to correspond in composition to the neutral Val imine. In terms of the pathway of Scheme 2, the final Htransfer from the nitrogen of the oxazolone is blocked by the methyl group of the N-methyl-glycine and N-methyl-alanine, with the result that neutral imine elimination is observed as the dominant primary fragmentation pathway of the b 2 ion.…”
Section: Mechanistic Considerationssupporting
confidence: 88%
“…Again, elimination of the neutral Tyr imine (135 u) to form m/z 100 is the major primary fragmentation pathway. A similar result has been reported by Wysocki and co-workers [47], who observed that the b 2 ion derived from Val-(N-methyl-Ala)-AlaPro-Arg fragmented exclusively by loss of a neutral of 71 u, which was shown to correspond in composition to the neutral Val imine. In terms of the pathway of Scheme 2, the final Htransfer from the nitrogen of the oxazolone is blocked by the methyl group of the N-methyl-glycine and N-methyl-alanine, with the result that neutral imine elimination is observed as the dominant primary fragmentation pathway of the b 2 ion.…”
Section: Mechanistic Considerationssupporting
confidence: 88%
“…missing because the radical ion does not contain leucine. The b 2 -H ion corresponds to abstraction of a hydrogen from the regular b 2 ion that is formed via a low-energy charge-directed dissociation channel [13,14,16,43,45,52]. These hydrogen-deficient b-type ions have been observed in previous radical ion fragmentation experiments [13,14,16,43,45].…”
Section: Radical-driven Fragmentation At Serine and Threoninementioning
confidence: 80%
“…In addition to chain length, it is highly likely that individual residues in the chain will influence the amide bond cleaved. In this respect, Wysocki and coworkers [23] have observed that doubly-protonated Val-Pro-AlaPro-Arg shows extensive cleavage at the N-terminal amide bond to form both y 4 and y 4 ϩ2 ions with only minor cleavage of the second amide bond. They also observed that doubly-protonated Val-Pro-Asp-Pro-Arg showed major cleavage C-terminal to the Asp residue to give the complementary b 3 and y 2 ions by charge separation.…”
Section: Discussionmentioning
confidence: 99%